Reclaiming Our Future - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2022)
The publication describes pathways to achieve more inclusive and sustainable post-pandemic recovery in Asia and the Pacific. It identifies elements for a common agenda for present and future generations centered on protecting people and planet, leveraging on digital opportunities, trading and investing more together, raising financial resources and managing debt. It underlines the need to listen and work with the youth, placing women at the center for crisis-prepared policy action and new people-centric partnerships, with a readiness of the Economic and Social Commission for Asia and the Pacific (ESCAP) to serve.